An overview of municipal information systems of Drakenstein municipality with reference to the Actionit open decision support framework - De Kock, Jacobus M. (Jacobus Michiel) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScEng)--University of Stellenbosch, 2002.